Unspoken Issues In Architectural Education - Dinçyürek, Özgür; Hoşkara, Şebnem Önal; Vural, Müjdem S. (Open House Int, 2015)
The international conference on Architectural Education, was held at the Faculty of Architecture, Eastern Mediterranean University (EMU) in Famagusta, North Cyprus, on April 3-4, 2014. This conference has been organized in collaboration with the European Association for Architectural Education (EAAE), under the title of “Unspoken Issues in Architectural Education (UIAE)”. The main aim of UIAE-2014 conference was to bring a wide range of people who are involved in architectural education together to discuss architectural education from various perspectives. Providing such an international scholarly platform was expected to open new horizons for the future of architectural education. Thus, under the title of the conference, discussions were carried on within the main themes of “Diversified Mediums”, “Dynamic Philosophy”, and “Contradictory Education”. The presented papers by the participation of more than hundred scholars, discussed and investigated key challenges of architectural education in present time such as; the (ir)relevance of architectural education to the real world, the effects of media, working or designing for poor, disaster management, climate change, fuel poverty, the price of energy, conflicts and wars, number of architects and architectural schools questioning the meth schools and many other thought-provoking issues. Amongst the presented papers, 10 best papers were selected by the session chairs and referees to be published in this special issue of Open House International Journal with the theme of Unspoken Issues in Architectural Education. odology of teaching in architecture, accreditation for architectural
The file in this item is the publisher version (published version) of the article.
Keywords: URBAN STUDIES; ENVIRONMENTAL STUDIES, ARCHITECTURE